Determinants influencing the entrepreneurial success of MSMEs in emerging economies: a study of Indian women entrepreneurs - Madhukara Nayak; Pushparaj M. Nayak; Harisha G. Joshi (Cogent Economics & Finance)
This study examines the influence of internal and external factors on the success of women entrepreneurs who own and manage Micro, Small, and Medium Enterprises (MSMEs) in India. A structured questionnaire was used to collect data from 700 women entrepreneurs using a simple random sampling technique to achieve the objectives. This research uses quantitative research methods to analyse data using the partial least squares (PLS) structural equation modeling (SEM) method. The study found that the need for achievement, risk-taking, self-confidence, financial, and socio-cultural factors significantly and positively influence the success of women entrepreneurs. Research on the factors influencing the success of women entrepreneurs is crucial for developing nations, particularly India. This study aims to address existing gaps in the literature by identifying new factors that contribute to the success of women entrepreneurship in emerging countries like India. The findings will be of use to policymakers and industry experts in designing appropriate policies and strategies to promote the untapped potential among women entrepreneurs in India.